1997
DOI: 10.1097/00001756-199703240-00015
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of neuropeptidergic sensory nerves in alopecia areata

Abstract: Alopecia areata (AA) is a dermatosis involving the sudden occurrence of bald patches on the scalp. Although the aetiology is unknown, experimental data indicate that cutaneous microcirculation plays an important role. The skin is richly innervated by neuropeptidergic sensory nerves that help regulate microvascular circulation. This study shows a reduction of cutaneous levels of substance P and calcitonin gene-related peptide (CGRP) but not of vasoactive intestinal polypeptide in scalp biopsies from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 5 publications
1
31
0
Order By: Relevance
“…Hordinsky et al [48] reported increased neuronal CGRP immunoreactivity around eccrine glands of AA patients, while Meyronet et al [49] found decreased immunoreactivity of skin and hair follicles in the areas of lesions compared to biopsies from healthy scalp regions. Lower levels of CGRP were detected when comparing biopsies from AA patients with those from healthy controls [50]. Other mediators like the neuropeptide neurotensin [51] or the corticotropin-releasing hormone (CRH) [52] via induction of mast cell degranulation might Representative examples of flourogold-traced dorsal root ganglia from nonstressed (e) and stressed mice (g).…”
Section: Discussionmentioning
confidence: 99%
“…Hordinsky et al [48] reported increased neuronal CGRP immunoreactivity around eccrine glands of AA patients, while Meyronet et al [49] found decreased immunoreactivity of skin and hair follicles in the areas of lesions compared to biopsies from healthy scalp regions. Lower levels of CGRP were detected when comparing biopsies from AA patients with those from healthy controls [50]. Other mediators like the neuropeptide neurotensin [51] or the corticotropin-releasing hormone (CRH) [52] via induction of mast cell degranulation might Representative examples of flourogold-traced dorsal root ganglia from nonstressed (e) and stressed mice (g).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated in the absence or presence of the indicated concentrations of recombinant bioactive ADM protein (rADM) 1,[30][31][32] (Merck Biosciences GmbH, Schwalbach, Germany), ADM receptor antagonist; Human Calcitonin Gene Related Peptide I [33][34][35] (Merck Biosciences GmbH, Schwalbach, Germany) for 48 hr. Then, 10 ll MTT (5 mg/ml in PBS) were added to each well and incubated for 4 hr at 37°C.…”
Section: Cell Growth Assays and Tgf-b1 Inductionmentioning
confidence: 99%
“…Alopecia areata (AA) is a common dermatosis that causes patches of nonscarring hair loss on the scalp or eyebrows, beard, and less frequently on other skin areas [60,61] . The autoimmune hypothesis is the most exam- ined, but the pathophysiology of AA appears complex [60] ; in 1994, Paus et al [61] demonstrated that substance P (SP) may play a role in the neural control of hair growth.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…The autoimmune hypothesis is the most exam- ined, but the pathophysiology of AA appears complex [60] ; in 1994, Paus et al [61] demonstrated that substance P (SP) may play a role in the neural control of hair growth. They suggested an interesting interaction in epithelial-mesenchymal-neuroectodermal system of the hair follicle.…”
Section: Alopecia Areatamentioning
confidence: 99%
See 1 more Smart Citation